Molecular theory of partial molar volume and its applications to biomolecular systems - Imai, T. (Condensed Matter Physics, 2007)
The partial molar volume (PMV) is a thermodynamic quantity which contains important information about
the solute-solvent interactions as well as the solute structure in solution. Additionally, the PMV is the most
essential quantity in the analysis of the pressure effect on chemical reactions. This article reviews the recent
developments in molecular theories of the PMV, especially the reference interaction site model (RISM) theory
of molecular liquids and its three-dimensional generalization version (3D-RISM), which are combined with the
Kirkwood-Buff solution theory to calculate the PMV. This article also introduces our recent applications of the
theory to some interesting issues concerning the PMV of biomolecules. In addition, theoretical representations
of the effects of intramolecular fluctuation on the PMV, which are significant for biomacromolecules, are briefly
discussed. Парцiальний молярний об’єм (PMV) є термодинамiчною величиною, яка мiстить важливу iнформацiю про взаємодiї розчинена речовина-розчинник, а також про структуру розчиненої речовини в розчинi. Крiм того, PMV є найбiльш суттєвою величиною при аналiзi впливу тиску на перебiг хiмiчної реакцiї. Ця стаття мiстить огляд сучасного стану молекулярних теорiй PMV, зокрема, молекулярної теорiї базисної моделi взаємодiючих центрiв (RISM) i її тривимiрного узагальнення (3D-RISM), якi, для обчислення PMV, є об’єднанi з теорiєю Кiрквуда-Баффа для розчинiв. Тут також представленi застосування теорiї для ряду випадкiв, що стосуються PMV бiомолекул. Ми також коротко обговорюємо вплив мiжмолекулярних флуктуацiй на PMV, який є важливими для бiомакромолекул.